Analisis Manajemen Keuangan dalam Kebijakan Pendidikan Gratis di Pondok Pesantren Ar-Rahmah Srandakan - Wulandari, Fransisca; Berliana, Adhe Sukma; Fitriah, Januari; Nugroho, Aji Wahyu; Setiawan, Farid (ALSYS, 2022)
The research entitled Analysis of Finacial Management in Free Education Policy at the Ar-Rahmah Srandakan Islamic Boarding School has the aim of describing and explaining the stages of financial management at the Ar-Rahmah Srandakan Islamic Boarding School, starting from budgeting, allocating funds, and procedures for managing free education funds in Islamic Boarding School, Bantul. The type of research used is field research with qualitative research methods. In terms of collecting information by using observation lines on an object, interviews with sources and gathering completeness of documentation. This study uses a triangulation technique, namely the disclosure of information results that have been carried out to data sources. The results obtained from observations show that financial management at the Ar-Rahmah Srandakan Islamic Boarding School is not in accordance with theories related to the financial implementation process. The financial reports used by the Ar-Rahmah Islamic Boarding School are still very simple. The treasurer keeps books of financial and income, reports on expenditures, and also allocates funds for activities/programs of Islamic Boarding School. The financial management is not in accordance with the theories in financial management, it is only regulated by the caretaker of the Islamic Boarding School with the help santri as the treasurer of the boarding school. The existence of a free education policy is fully funded by KH. Abdul Rozak Fachrudin and his family so that the implementation of the policy is still well realized. The aim is to develop the morals and character of the children victims of the Ambon and Kupang riots so that they can get a proper education and help the underprivileged in sending their children to school.